Food structure : its creation and evaluation - Blanshard, J. M. V.; Mitchell, J. R., Ph. D. (Butterworths, 1988)
Food Structure-Its Creation and Evaluation reviews research and major developments with regard to the role of ingredients in building food structures. Emphasis is on homogeneous and heterogeneous multicomponent systems, their molecular interactions, the macroscopic physics of their mechanical properties, and the variety of techniques and strategies necessary to evaluate their properties if they are to be acceptable to the consumer. This book is comprised of 26 chapters and begins by discussing the relevance of food structure from a dental clinical perspective. The next chapter describes a hier.